Age- and gender-specifi c patterns of adolescent crisis manifestations - Vasilenko, Victoria Evgenievna (Известия Саратовского университета. Новая серия: Акмеология образования. Психология развития)
The relevance of this study stems from the increasing diversity of trajectories of modern adolescents’ development, as well as the need for a diff erentiated approach to studying the teenage crisis based on age and gender. The research aims to identify manifestations of the adolescent crisis across diff erent ages and genders. The hypotheses are as follows: 1) manifestations of the adolescent crisis begin to appear in modern adolescents as early as 10–11 years old, with the critical phase occurring at 13–14 years old (grades 7–8); 2) gender diff erences in crisis symptoms depend on the phase of the crisis; and 3) the formation of the image of adulthood in adolescents, infl uenced by age and gender patterns, is weakly expressed due to high individual variability. Participants: the study analyzed symptoms of the adolescent crisis in 508 adolescents (209 boys and 299 girls; 477 teenagers were from St. Petersburg, 20 teenagers were from Krasnoyarsk, 11 teenagers were from Sochi) aged 10 to 17 years (SD = 14). The sample was divided into three age groups: 10–12 years old (n = 106), 13–14 years old (n = 150), and 15–17 years old (n = 252), as well as by school grades: grades 5–6 (n = 124), grades 7-8 (n = 154) and grades 9–10 (n = 230). Additionally, essays on growing up were collected from 204 adolescents. Methods (tools): the survey of adolescent crisis symptoms (V. E. Vasilenko), and the methodology for studying the image of adulthood (O. V. Kurysheva, K. N. Polivanova). Results: ages 10-12 (grades 5-6) represent a precritical phase, ages 13–14 (grades 7–8) constitute a critical phase, and ages 15–17 (grades 9–10) mark a post-critical phase. Gender diff erences are less pronounced during the critical phase. In general, boys are more prone to emancipation and grouping reactions, while girls are more prone to hypercompensation and interest in the inner world. Diff erences in the image of adulthood are observed primarily between the younger and older groups. The second type – “the real plan of action is external adulthood” – prevails across all groups. At ages 15–17, girls demonstrate a more developed image of adulthood compared to boys. Main conclusions: on average, the peak of the adolescent crisis occurs at ages 13–14. The formation of the image of adulthood progresses at a slow pace, with gender diff erences being less pronounced. Practical significance: understanding age- and gender-specifi c patterns of the adolescent crisis can be valuable for the psychological support during adolescents’ transition to adulthood.